Penetration of polydimethylsiloxanes (PDMS) to nervous tissue of rats - Łukasiak, J.; Jachowska, D.; Jamrogiewicz, Z.; Morys, J.; Prokopowicz, M.; Czarnobaj, K.; Falkiewicz, B. (Polimery, 2022)
Penetration of various forms of PDMS from alimentary tract of rats to their blood, urine and brain has been described. The groups or rats were supplied with PDMS either with food or directly to the stomach (tables 1 and 2). Possibility of organism penetration (espescially nervous tissue) with PDMS using lymphatic path has been proposed.